PERHITUNGAN HARGA POKOK PRODUKSI BERDASARKAN METODE HARGA POKOK PESANAN PADA USAHA CAHAYA MATA DI KECAMATAN BLANG MANGAT KOTA LHOKSEUMAWE - Dika Handayani, Musfiana, Irma Anggraini (Jurnal Economica Didactica, 2019)
ABSTRACTThis research is entitled "Calculation Production cost Based on the methode of Order On Usaha Cahaya Mata in Blang Mangat Sub-District of Lhokseumawe". Usaha Cahaya Mata in Blang Mangat sub-district of Lhokseumawe is a company engaged in embroidery fabric.Usaha Cahaya Mata performs its production activities based on orders from consumers. Specifically, in this study aims to calculate (1) the cost of production based on monthly order cost method at Usaha Cahaya Mata in Blang Mangat subdistrict of Lhokseumawe city, (2) monthly sales result at Usaha Cahaya Mata in Blang Mangat sub-district of Lhokseumawe city and (3) monthly net profit on Usaha Cahaya Mata Business in Blang Mangat sub-district of Lhokseumawe. In conducting this research, will be used descriptive method with qualitative approach which is processing data to obtain data in the form of numbers also explain and describe phenomena which will be studied. The source for this data research data is from Usaha Cahaya Mata, while data source is business owner of Cahaya Mata in Blang Mangat Subdistrict of Lhokseumawe City. Data collection is done by documentation and direct interview with business owner of Cahaya Mata about company activity and calculation of cost of goods manufactured. In order for the observation data can be trusted, the writer used recording tool in the form of stationery and electronic media. The results of this study show that the production cost in March 2018 on Usaha Cahaya Mata in Blang Mangat subdistrict of Lhokseumawe is Rp. 47.59 million. On March 2018 sales results conducted by Usaha Cahaya Mata in Blang Mangat Subdistrict of Lhokseumawe is Rp. 54.000.000 and net profit of March 2018 which obtained by Usaha Cahaya Mata in Blang Mangat subdistrict of Lhokseumawe is Rp. 5.910.000.Keywords: The Calculation Of Production Cost Of Usaha Cahaya Mata.